(untitled) (Journal of Dhaka Medical College, 2023)
Background: Apart from being suffered from the Coronavirus disease 2019 (COVID-19), the pandemic has been associated with mental health conditions related to the fear of being affected by the virus, relative insufficiency of the healthcare system and the alleviating measures. We aimed to determine the types and associated sociodemographic factors of first episode psychosis (FEP) occurred during COVID-19 pandemic. Materials and methods: This was a cross-sectional study carried out at the outpatient department of National Institute of Mental Health (NIMH), Bangladesh. Individuals whose psychiatric symptoms were noticed for the first time during the covid outbreak, were included in the study using a convenient sampling technique during September, 2020 - December, 2020. After having informed written consent, data were collected through face-to-face interview of the respondents using a semistructured questionnaire. Psychotic features were elicited and psychiatric diagnoses were assigned by qualified psychiatrists after a thorough assessment according to Diagnostic and Statistical Manual of Mental Disorders, version 5 (DSM-5). Completed data of 288 respondents were analyzed using Statistical Package for Social Sciences (SPSS), version 24. The institutional review board of NIMH approved the research. Results: About three-fifths (58.3%) of the respondents suffered from first episode psychosis. Around half (47.0%) of the patients with psychosis was suffering from schizophrenia spectrum and other psychotic disorders and 39.3% from bipolar and related disorders. Majority (36.2%) of the respondents with FEP belonged to the age group of 20-29 years, with the mean age of 28.01±12.859 years. There was a significant association between gender and the presence of psychosis (p<.05). Conclusion: Majority of the FEP were schizophrenia spectrum and other psychotic disorders having a younger age of onset. J Dhaka Med Coll. 2021; 30(2) : 220-226